2017
DOI: 10.15384/kjhp.2017.17.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior and Nutrient Intake in Metabolically Abnormal Overweight and Metabolically Abnormal Obesity

Abstract: Background:The purpose of this study was to investigate the differences in health behaviors and dietary habits between the metabolically healthy group and the metabolically abnormal group in overweight and obese subjects based on the data of National Health and Nutrition Survey (NHANES). Methods: Using the NHANES data (2007)(2008)(2009)(2010), a total of 18,188 subjects were grouped into the metabolically healthy group and the abnormal group using the National Cholesterol Education Program Adult Treatment Pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Korea, the 10–20 year old group consumes the most sugar, and sugar-sweetened beverages are the major source of sugar intake from processed foods, the largest proportion of which was carbonated drink consumption [ 20 ]. Pae et al [ 21 ] reported the association between frequent carbonated drink consumption and women’s obesity. However, studies on the relationship between carbonated drink consumption and MetS incidence are infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the 10–20 year old group consumes the most sugar, and sugar-sweetened beverages are the major source of sugar intake from processed foods, the largest proportion of which was carbonated drink consumption [ 20 ]. Pae et al [ 21 ] reported the association between frequent carbonated drink consumption and women’s obesity. However, studies on the relationship between carbonated drink consumption and MetS incidence are infrequent.…”
Section: Introductionmentioning
confidence: 99%